PROSES KREATIF (STRUKTUR TEKNIK KARYA LUKISAN) DEWA MADE MUSTIKA - Syamsiar, Syamsiar (Institut Seni Indoensia Surakarta, 2019)
AbstractThis study aims to describe the ceative process (techniques and structures) of Dewa Made Mustika’s paintings in 1994-2018. Dewa Made Mustika is a man born in Tegalalang, Gianyar, Bali, on August 25, 1974. He grew up in Bali and continued his art education at the Indonesian Institute of Arts Yogyakarta in 1994 and graduated in 2000. The creative process of Dewa Made Mustika, reflected in his paintings, is interesting because the energy that exists in the creative process is extraordinary over time. His work on display at the Cultural Park of Yogyakarta in 2017 showed a remarkable energy, not only big that reaches 2800 cm long and 280 cm wide but also with excellent expressive-figurative cultivation technique. If the work of Dewa Made Mustika has tremendous energy at this time, then what about-the works that were created at the beginning of the study at the Indonesian Institute of Arts Yogyakarta up to his present super jumbo works, how the shape structure, the coloring and the techniques used in order to give an idea of how the creative process takes place. This is important for artists from an arts institute to become inspiration in learning the progress of a successful artist in developing his career. The research technique used is descriptive research technique by collecting data based on the facts, summarizes the existing data and presenting it.Keywords: Creative Process, Structure, technique, Paintings, Dewa Made Mustika